International Lung Cancer Consortium: pooled analysis of sequence variants in DNA repair and cell cycle pathways - Hung, Rayjean J; Christiani, David C; Risch, Angela; Popanda, Odilia; Haugen, Aage; Zienolddiny, Shan; Benhamou, Simone; Bouchardy, Christine; Lan, Qing; Spitz, Margaret R; Wichmann, H-Erich; LeMarchand, Loic; et al. (Cancer epidemiology, biomarkers & prevention, 2008)
The International Lung Cancer Consortium was established in 2004. To clarify the role of DNA repair genes in lung cancer susceptibility, we conducted a pooled analysis of genetic variants in DNA repair pathways, whose associations have been investigated by at least 3 individual studies. Data from 14 studies were pooled for 18 sequence variants in 12 DNA repair genes, including APEX1, OGG1, XRCC1, XRCC2, XRCC3, ERCC1, XPD, XPF, XPG, XPA, MGMT, and TP53. The total number of subjects included in the analysis for each variant ranged from 2,073 to 13,955 subjects. Four of the variants were found to be weakly associated with lung cancer risk with borderline significance: these were XRCC3 T241M [heterozygote odds ratio (OR), 0.89; 95% confidence interval (95% CI), 0.79-0.99 and homozygote OR, 0.84; 95% CI, 0.71-1.00] based on 3,467 cases and 5,021 controls from 8 studies, XPD K751Q (heterozygote OR, 0.99; 95% CI, 0.89-1.10 and homozygote OR, 1.19; 95% CI, 1.02-1.39) based on 6,463 cases and 6,603 controls from 9 studies, and TP53 R72P (heterozygote OR, 1.14; 95% CI, 1.00-1.29 and homozygote OR, 1.20; 95% CI, 1.02-1.42) based on 3,610 cases and 5,293 controls from 6 studies. OGG1 S326C homozygote was suggested to be associated with lung cancer risk in Caucasians (homozygote OR, 1.34; 95% CI, 1.01-1.79) based on 2,569 cases and 4,178 controls from 4 studies but not in Asians. The other 14 variants did not exhibit main effects on lung cancer risk. In addition to data pooling, future priorities of International Lung Cancer Consortium include coordinated genotyping and multistage validation for ongoing genome-wide association studies.